2014
DOI: 10.1158/1055-9965.epi-14-0177
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Insulin-like Growth Factor I Receptor and Altered Insulin Receptor Isoform mRNAs in Normal Mucosa Predict Colorectal Adenoma Risk

Abstract: Background Hyperinsulinemia resulting from obesity and insulin resistance is associated with increased risk of many cancers, but the biology underlying this risk is unclear. We hypothesized that increased mRNA levels of the insulin-like growth factor 1 receptor (IGF1R) versus the insulin receptor (IR) or elevated ratio of IR-A:IR-B isoforms in normal rectal mucosa would predictadenoma risk, particularly in individuals with high body mass index (BMI) or plasma insulin. Methods Biopsies from normal rectal muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Rat models have demonstrated that insulin can induce proliferation of colorectal epithelial cells and the development of aberrant crypt foci, the primary neoplastic lesions in colorectal development ( 39 ). In colonic tumor cells, the expression of the insulin receptor protein is elevated, particularly isoform A, which exerts mitogenic effects ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rat models have demonstrated that insulin can induce proliferation of colorectal epithelial cells and the development of aberrant crypt foci, the primary neoplastic lesions in colorectal development ( 39 ). In colonic tumor cells, the expression of the insulin receptor protein is elevated, particularly isoform A, which exerts mitogenic effects ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, glycemic index and glycemic load, which are alternative concepts to quantify the impact of carbohydrate-foods on postprandial glucose responses [19], have also been shown to be unrelated to colorectal cancer and adenoma risk in a systematic review [20]. Moreover, a recent US case-control study documented an unexpected inverse association between IGF-1 receptor levels and colorectal adenoma risk [21], thereby conflicting with earlier evidence of a direct association with colorectal cancer risk [7]. Collectively, the biological and epidemiological evidence to date appear to be contrasting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to breast cancer, in squamous cell lung carcinoma, high INSR-A:INSR-B ratio was associated with lower epithelial-mesenchymal transition (EMT) gene signature and longer survival ( 56 ). A recent case control study of colorectal adenoma in patients found no difference in the total INSR mRNA; however, in patients with high plasma insulin, increased INSR-A:INSR-B ratio was associated with increased likelihood of having adenomas ( 79 ). Therefore, the usefulness of INSR-A:INSR-B ratio likely varies by tumor type and should be evaluated separately.…”
Section: Insr-a:insr-b Ratio As a Cancer Biomarkermentioning
confidence: 96%